2008
DOI: 10.1159/000182891
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Gene-Gender Effects of Adrenergic Polymorphisms on Hypothalamic-Pituitary-Adrenal Axis Activity in Depressed Patients

Abstract: Objective: There is overwhelming evidence that activation of the hypothalamic-pituitary-adrenal (HPA) system plays a major role in depression and cardiovascular disease in genetically susceptible individuals. We hypothesized that due to the multiple interactions between the sympathetic and the HPA systems via adrenoceptors, polymorphisms in these genes could have an impact on HPA axis activity in major depression. Methods: Using the dexamethasone/corticotrophin-releasing hormone (DEX/CRH) test, we investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Another example is gender; given the difference between sexes, certain genetic risk factors can be expected to affect males and females differently. That this affects association studies has already been shown in ADHD (Biederman et al 2008; Guimaraes et al 2007; Rommelse et al 2008b) as well as other (related) psychiatric disorders (Craig et al 2004; Diamond 2007; Haefner et al 2008; Kendler 1998; Lang et al 2008; Okamura et al 2007; Rucci et al 2009). An additional potentially important factor is age at diagnosis.…”
Section: Reviewmentioning
confidence: 90%
“…Another example is gender; given the difference between sexes, certain genetic risk factors can be expected to affect males and females differently. That this affects association studies has already been shown in ADHD (Biederman et al 2008; Guimaraes et al 2007; Rommelse et al 2008b) as well as other (related) psychiatric disorders (Craig et al 2004; Diamond 2007; Haefner et al 2008; Kendler 1998; Lang et al 2008; Okamura et al 2007; Rucci et al 2009). An additional potentially important factor is age at diagnosis.…”
Section: Reviewmentioning
confidence: 90%
“…Study inconsistencies may be related to timing of cortisol assessments or may reflect methodological confounds, such as age of study subjects (e.g., post-menopausal women differ from premenopausal women and thus sex differences differ), chronicity of illness (e.g., sustained illness may produce blunted cortisol response rather than hypercortisolemia), or low statistical power to detect sex differences which may vary in effect size, depending on characteristics of the sample (details next paragraph). Further, genetic background likely affects HPA axis dysregulation, as demonstrated in studies showing increased ACTH and cortisol in males (but not females) homozygotic for the alpha (2)-adrenoreceptor gene and females (but not males) homozygotic for the beta (2)-adrenoreceptor gene (Haefner et al, 2008). Collectively, these findings offer initial evidence of sex differences in the role of HPA axis in MDD pathophysiology and emphasize the importance of considering genetic variation in HPA axis-associated genes.…”
Section: Hpa Axis Implicated In Mddmentioning
confidence: 99%
“…Our unexpected findings lead us to speculate about contributions from the many complex effects involved in HPA axis reactivity and to conclude that the Dex/CRH test cortisol response may not be a useful tool for evaluating the potential effectiveness of antidepressants on HPA axis downregulation in healthy volunteers. Recent data describing gene–gender effects on Dex/CRH test response (Haefner et al 2008) suggest a further avenue of research inquiry for understanding our results.…”
Section: Discussionmentioning
confidence: 92%
“…These findings are important, given the extensive use of the Dex/CRH test for assessing HPA axis function in a variety of pathological conditions and for studying the mechanism of action of numerous therapeutic agents. A growing literature has identified a collection of clinical and demographic variables exerting significant effects on the cortisol response to the Dex/CRH test, including age (Kunugi et al 2006), sex (Haefner et al 2008), temperament (Tyrka et al 2008b), coping style (Hori et al 2010), early life adversity (Carpenter et al 2009b; Heim et al 2008), quality of parental care (Tyrka et al 2008a), adult trauma exposure (Klaassens et al 2009), social support (Tsuru et al 2008), psychiatric comorbidity (Veen et al 2009), and genotype (Binder et al 2010; Tyrka et al 2009; Zobel et al 2010). Assumptions about qualitatively similar cellular and system-level responses to receptor activation by sertraline across depressed and healthy subjects supported the rationale for this investigation.…”
Section: Discussionmentioning
confidence: 99%